2022
DOI: 10.5195/ijt.2022.6450
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Goal Achievement When Transitioning from In-Person Therapy to Teletherapy in the Westchester County Early Intervention Program Due to the COVID-19 Pandemic

Abstract: The sudden transition to virtual therapeutic services during the COVID-19 pandemic provided a unique opportunity to explore telehealth as a platform for delivering early intervention (EI) services. Through retrospective chart review of 93 children, we collected the following data: demographics, diagnosed conditions, therapy type, service format, and provider-reported participant goal achievement (1=no progress, 2=little progress, 3=moderate progress, 4=great deal of progress, 5=outcome achieved) over a six-mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Though the disruption to EI services and sudden conversion to teletherapy likely affected these outcomes, exploring the effectiveness of EI services was outside the scope of this study. A few studies on teletherapy during COVID-19 have reported similar achievements compared to in-person sessions, especially with family centered coaching practices and provider training on teletherapy (12,24,25). Furthermore, studies have reported other bene ts of teletherapy as a substitute for in-person visits during the pandemic, such as reduced stress in the home environment, increased caregiver involvement, exibility of scheduling and accessibility of services for remote areas, that may have offset some negative effects of teletherapy delivery (8, 12,24,25).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Though the disruption to EI services and sudden conversion to teletherapy likely affected these outcomes, exploring the effectiveness of EI services was outside the scope of this study. A few studies on teletherapy during COVID-19 have reported similar achievements compared to in-person sessions, especially with family centered coaching practices and provider training on teletherapy (12,24,25). Furthermore, studies have reported other bene ts of teletherapy as a substitute for in-person visits during the pandemic, such as reduced stress in the home environment, increased caregiver involvement, exibility of scheduling and accessibility of services for remote areas, that may have offset some negative effects of teletherapy delivery (8, 12,24,25).…”
Section: Resultsmentioning
confidence: 98%
“…A few studies on teletherapy during COVID-19 have reported similar achievements compared to in-person sessions, especially with family centered coaching practices and provider training on teletherapy (12,24,25). Furthermore, studies have reported other bene ts of teletherapy as a substitute for in-person visits during the pandemic, such as reduced stress in the home environment, increased caregiver involvement, exibility of scheduling and accessibility of services for remote areas, that may have offset some negative effects of teletherapy delivery (8, 12,24,25). Further studies are needed to understand the lasting impact of COVID-19 restrictions and explore strategies that best support at risk populations.…”
Section: Resultsmentioning
confidence: 98%
“…It is well known that during the COVID-19 pandemic, many healthcare facilities and therapy centers were forced to limit in-person services due to safety concerns and lockdown measures. (42,43) This disruption could have potential implications for access to speech, occupational, and physical therapy services for former preterm infants, and may have impacted their neurodevelopment.…”
Section: Limitationsmentioning
confidence: 99%